Analysis of simple sequence repeat markers linked to submergence tolerance on newly developed rice lines derived from MR263 × Swarna-Sub1 - Welland Cosmas Mojulat,; Mohd Rafii Yusop,; Mohd Razi Ismail,; Abdul Shukor Juraimi,; Abdul Rahim Harun,; Fahim Ahmed,; Tanweer, Fatah Abro; Latif, Md Abdul (Penerbit Universiti Kebangsaan Malaysia, 2017)
Nowadays, in extreme changing environments, development of submergence tolerance variety is necessary for ensuring crop production stability where, it is known that Malaysian commercial rice varieties such as MR219, MR220 and MR263 were severely susceptible to submergence. First step towards the development of submergence tolerance variety starts with the breeding program by crossing MR263 and Swarna-Sub1. Marker-assisted selection (MAS) was carried out through the utilization of simple sequence repeats (SSR) markers, considering its reliability as pre-selection tools to conduct this research. F1 generations plants were confirmed by tightly linked markers. In case of background study, out of 180 SSR markers, 38 were found polymorphic between two parents. Association of molecular markers and submergence tolerance were determined using Chi-square test. MR263 × Swarna-Sub1 F2 lines were tested for Sub1 gene conformation using the markers RM8300 and RM219. These markers showed a good fit to the expected marker segregation ratio (1:2:1) in a Mendelian single gene model (DF=1.0, p≤0.05). Eleven homozygous lines with Sub1 gene out of 256 were selected for future development of submergence tolerant varieties. Eleven lines were selected based on phenotypic study and agronomic performance.